Evaluation of conservation and trade status of marine ornamental fish harvested from Pangandaran Coastal Waters, West Java, Indonesia - Agus Nuryanto; DIAN BHAGAWATI; KUSBIYANTO (Society for Indonesian Biodiversity, 2020)
Abstract. Nuryanto A, Bhagawati D, Kusbiyanto. 2020. Evaluation of conservation and trade status of marine ornamental fish harvested from Pangandaran Coastal Waters, West Java, Indonesia. Biodiversitas 21: 512-520. Pangandaran coastal waters are among the main supply areas of marine ornamental fish in Indonesia. However, no scientific data are available on the conservation and trade status of marine ornamental fish harvested in this region. This study aimed to evaluate the diversity, conservation, and trade status of marine ornamental fish species harvested from Pangandaran coastal waters. Fish were collected during surveys conducted in March, April, July, and September 2019. Species were identified by referring to the available guidance books. The conservation status was analyzed according to the IUCN database, whereas the trade status was evaluated based on the CITES database. A total of 107 marine ornamental fish species from 32 families and eight orders was obtained. The two out of these 107 species had an unresolved conservation status, whereas 24 species were listed as Not Evaluated, 80 species were listed as Least Concern, and one species was listed as Vulnerable by IUCN. Two species had an unknown trade status, whereas 104 species were listed as Not Evaluated and one species was listed in Appendix II of CITES. Our data prove that Pangandaran coastal waters have a high potential for supplying marine ornamental fish, with most of the species listed as having a Not Evaluated or Least Concern status. Most of the species identified were also categorized as having a Not Evaluated trade status.